Time-Frequency-Based Speech Regions Characterization and Eigenvalue Decomposition Applied to Speech Watermarking. (15th August 2010) - Orović Orović, Irena Irena; Stanković Stanković, Srdjan Srdjan
Abstract : The eigenvalues decomposition based on the S-method is employed to extract the specific time-frequency characteristics of speech signals. This approach is used to create a flexible speech watermark, shaped according to the time-frequency characteristics of the host signal. Also, the Hermite projection method is applied for characterization of speech regions. Namely, time-frequency regions that contain voiced components are selected for watermarking. The watermark detection is performed in the time-frequency domain as well. The theory is tested on several examples.